A Comparison between Natural Pozzolana and Fly Ash Replacements on the Mechanical Properties of Concrete - Aburumman, Mervat O.; Al-diseet, Malak M.; O., MohsenMohamed; Abdel-Jaber, Mu’tasim; Naji, Khalid Kamal A A; Abu Taqa, Ala (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2023)
This study investigates the effect of Natural Pozzolana (NP) and Fly Ash (FA) substitutes on concrete’s mechanical and microstructural properties. Mixes containing 10 - 50 % cement substitute ratios were prepared and tested for flexure and compressive strength after 28 days of curing. Then, qualitative microstructural analysis was performed using Scanning Electron Microscope (SEM). In terms of compressive strength, the mixes containing only 10 % replacement ratios of both NP and FA showed an improvement of 10 % compared to the plain control mix. On the other hand, all mixes containing FA could attain at least a 25 % development in their flexural strength compared to the control mix. The microstructural analysis illustrated that adding FA and NP enhances cement hydration by improving the formation of dense hydration products such as calcium silicate hydrate (C-S-H) and calcium hydroxide (C-H), which are mainly responsible for the performance of the improved mechanical properties of concrete.